An experimental study on social anchoring - Lukas Meub; Till Proeger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
The anchoring-and-adjustment heuristic has been studied in numerous experimental settings and is increasingly drawn upon to explain systematically biased decisions in economic areas as diverse as auctions, real estate pricing, sports betting and forecasting. In these cases, anchors result from publicly observable and aggregated decisions of other market participants. However, experimental studies have neglected this social dimension by focusing on external, experimenter-provided anchors in purely individualistic settings. We present a novel experimental design with a socially derived anchor, monetary incentives for unbiased decisions and feedback on performance to more accurately implement market conditions. Despite these factors, we find robust effects for the social anchor, an increased bias for higher cognitive load, and only weak learning effects. Finally, a comparison to a neutral, external anchor shows that the social context increases the bias, which we ascribe to conformity pressure. Our results support the assumption that anchoring remains a valid explanation for systematically biased decisions within market contexts.
Keywords: C9; D8; Z1; 330; anchoring; conformity; heuristics and biases; incentives; laboratory experiment